Preliminary Study on the Effect of Nitrogen and Potassium Fertilization on Phytochemical Content Quality of Gynura procumbens - Mohamad Fhaizal, Mohamad Bukhori; Hawa ZE, Jaafar; Ali, Ghasemzadeh; Uma Rani, Sinniah; Gayatri, Karipaya (UTM Press, 2021)
Gynura procumbens is an herbaceous plant. Despite the progressive reports on the pharmacological properties, many are overlooking at the importance of agronomic requirements, such as fertilization, to produce high phytochemical content which have not been conclusively concluded. The study was carried out to examine the effects of N and K interaction on physiological and phytochemical quality; to identify compositions of phytochemicals, and to determine marker compounds. Physiological and phytochemical attributes were recorded in three harvests of triplicate samples to exhibit the trend for plant quality, and statistically analyzed. Generally, N and K interaction have affected phytochemical content significantly (p<0.05) with stronger effect on physiological and biochemical attributes (p<0.01). The results have demonstrated that the following combination of fertilizer, 0 kg/ha N and 30 kg/ha K; and 90 kg/ha N and 0 kg/ha K are high and low, respectively affecting metabolite content in the plant. Lowest rate of N, moderate of K had produced significant phytochemical contents. Meanwhile, caffeic acid and kaempferol were demonstrated as marker compounds in this study. Thus, phytochemical content can be further established through the selection of appropriate N and K rates and proper abiotic stress interaction.